Model Pembelajaran Make a Match untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas IV SD Negeri 2 Tomohon - Agnes M. Goni (Peneliti.net, 2022)
The purpose of this study was to improve the learning outcomes of fourth grade students of SD Negeri 2 Tomohon through the Make A Match Type Cooperative learning model. This research uses Classroom Action Research (CAR) which consists of four stages, namely (1) planning, (2) implementation, (3) observation, (4) reflection. Data collection techniques through observation techniques and student learning outcomes tests. The achievement of student results in the first cycle was 57.64%, the second cycle obtained 85.00% results, so that learning can be said to be successful in accordance with the expected goals so that this research stopped in the second cycle. Thus, it can be concluded that using the Make A Match Type Cooperative Learning Model can improve mathematics learning outcomes for fourth grade students of SD Negeri 2 Tomohon. So it is suggested that in order to improve student achievement, teachers should train students more by using varied learning models or approaches.